Computational analysis reveals historical trajectory of East Polynesian lunar calendars - Miguel Valério; Fabio Tamburini; Michele Corazza (PLoS ONE, 2026)
We investigate a type of lunar calendar known as lists of the ‘nights of the moon’, found throughout East Polynesia, including Rapa Nui (Easter Island). Using computational methods, we analyzed the lexical and structural divergence of 48 calendrical lists from all major archipelagos, each containing about 30 night names. Our results, presented as a rooted phylogenetic tree, show a split into two main groups: one including lists from Rapa Nui, Mangareva, and the Marquesas; the other comprising lists from New Zealand, Hawai’i, the Cook Islands, the Austral Islands, Tahiti, and the Tuamotu. This result aligns with a recent alternative classification of East Polynesian languages into ‘Distal’ (Marquesan, Mangarevan, Rapanui) and ’Proximal’ (Māori, Hawaiian, Tahitian, etc.) subgroups. Since both language and lunar calendars are symbolic systems passed down and changed within communities—and given the geographic isolation of many archipelagos—we interpret this correspondence as evidence that the early divergence of East Polynesian lunar calendars mirrors early population movements and language splits in the region.